Peter Hitchens’ Views on Political and Media Issues in an Interview with Michael Simmons on Spectator TV - Fatema Miah (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
An exoneration occurs when a person who has been convicted and punished for a crime is later officially declared innocent based on new and credible evidence. In such cases, the original conviction is overturned after the discovery of evidence that demonstrates the individual did not commit the alleged offense. Exonerations may result from various legal processes, including retrials, reinvestigations, and the re-examination of key evidence presented during the original proceedings. One significant factor often identified in wrongful convictions is the presence of false confessions obtained during police interrogations. Psychological research and legal studies have shown that confessions may sometimes be given under coercion, intimidation, or psychological pressure, rather than as voluntary admissions of guilt. These circumstances can lead individuals to confess to crimes they did not commit, thereby contributing to miscarriages of justice. Therefore, the examination of interrogation practices, the reliability of confession evidence, and the application of legal safeguards are essential in preventing wrongful convictions and ensuring fairness in the criminal justice system.